2021
DOI: 10.1016/j.ijchp.2021.100228
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Spanish Healthy Lifestyle Questionnaire

Abstract: Background/Objective : It is essential to carry out a diagnosis of people’s healthy lifestyles, in order to apply strategies to improve them. The aim of the study was to validate the Healthy Lifestyles Questionnaire (CEVS-II), collecting all factors that make up the concept of a healthy lifestyle, such as a balanced diet, respect for mealtimes, tobacco consumption, rest habits, alcohol consumption, other drug use and physical activity. Method : The questionnaire was completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 39 publications
1
11
0
7
Order By: Relevance
“…They conducted studies in Port Saied, Benha, and Sohag in Egypt, respectively, and reported that there was a positive correlation between total knowledge score and total practice score in pre and post training programs. This study is in agreement with Leyton et al (2021), who conducted a study in Brazil and Tashale and Alemu (2019). They found a significant positive correlation between the knowledge score and practice score of first aid and factors associated with practice among taxi drivers (r = 0.350, p = 0.05).…”
Section: Discussionsupporting
confidence: 93%
“…They conducted studies in Port Saied, Benha, and Sohag in Egypt, respectively, and reported that there was a positive correlation between total knowledge score and total practice score in pre and post training programs. This study is in agreement with Leyton et al (2021), who conducted a study in Brazil and Tashale and Alemu (2019). They found a significant positive correlation between the knowledge score and practice score of first aid and factors associated with practice among taxi drivers (r = 0.350, p = 0.05).…”
Section: Discussionsupporting
confidence: 93%
“…Pode-se observar, na tabela 2, os itens traduzidos com ajustes e sua respectiva retrotradução. Tanto a construção de uma escala quanto sua adaptação para outro contexto cultural necessitam da avaliação de especialistas para que seja possível certificar-se de que os itens do instrumento sejam capazes de ascender às qualidades teoricamente desejadas (Cervilla et al, 2021;Leyton-Roman et al, 2021). E o primeiro passo constitui a evidenciação da validade do conteúdo dos itens expostos (Muñiz & Fonseca-Pedredo, 2019).…”
Section: Resultsunclassified
“…The new challenges may affect an individual’s eating self-efficacy and consequently lead to weight loss failure. It is crucial for healthcare professionals to assess and acknowledge this issue not only to enhance weight management approaches but also to improve the community’s lifestyle in general by being equipped with the necessary tools and knowledge of the newly distinguished field of lifestyle medicine such as the Healthy Lifestyle and Personal Control Questionnaire (HLPCQ) [ 77 , 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%